Symptom correlations of organic brain impairment and psychopathology in patients with residual schizophrenia - D. N. Safonov (Kazimierz Wielki University, 2020)
Relevance. Organic brain impairment (OBI) is one of the most well studied comorbid pathology to schizophrenia. Nevertheless it is not clear yet, how it influences some structural and dynamic aspects of main pathology, such as positive symptoms variability and intensity or negative symptoms progression. Aim - to analyze influence of most common types of organic brain impairment and intensity of residual schizophrenia symptoms. Materials and methods. A study was performed on 100 case histories of patients of Zaporozhye Regional Clinical Psychiatric Hospital who were treated as inpatients with diagnosis of recurrent schizophrenia (ICD-10:F20.5) in time period from 2010 to 2020. Results. On the first stage of a study we studied contingent's medical history focusing on probable organic brain impairment inducing factors: cerebrovascular catastrophes, cerebrovascular diseases and cerebrovascular conditions.  We gathered clinical data on intensity of main positive and negative recurrent schizophrenia symptoms. Among positive symptoms rating in study contingent only conceptual disorganization reaches moderate level of intensity. Negative symptoms among studied patients have higher average intensity than positive with evenly moderate levels with exceptions of difficulty in abstract thinking and stereotyped thinking. We analyzed correlations between organic brain impairment inducing factors and positive and negative syndromes scale categories intensity rating. For correlation statistical interpretation we used Chaddock scale. Only weak correlations were found between positive symptom ratings and OBI inducing factors correlations both positive and negative. For negative symptom ratings we have found all weak correlations but one (traumatic brain injury have moderate negative correlation with conceptual disorganization). Conclusions. Analysis of correlations between organic brain impairment inducing factors with positive and negative symptoms revealed controversial data but definitely demonstrated presence of weak up to moderate influence of organic brain impairment on positive and negative symptom intensity.  However this influence is both positive and negative according to specific symptom as well as specific organic brain impairment variant.